The Effects of Self-Regulated Strategy Development (SRSD) Instruction on EFL Learners’ Autonomy and Writing Proficiency - Dony Marzuki; Sariani; Sumira (International Journal of English and Applied Linguistics (IJEAL), 2023)
This quasi-experimental study investigated the effects of self-regulated strategy development (SRSD) instruction on learners’ autonomy and writing proficiency in a university-level English program in Indonesia. Two intact classes of English students were involved in the study. They were in their second semester learning English Writing, a compulsory topic in their department. Within one semester, participants in the experiment group were trained with SRSD to improve their autonomous learning and writing proficiency. A comparison group learning the same topic without the SRSD training was also assigned. Data were gathered in two ways: a questionnaire for assessing learners’ autonomy and pretest and posttest writing tasks for assessing writing proficiency. Jamovi Software, an open-access statistical tool, was used to analyse the data. The results showed that the experiment groups' learning autonomy and writing proficiency improved significantly and outperformed the control group. The effect sizes of the analysis ranged from medium to large. The study’s results contribute to research and practice on EFL learners’ autonomy and writing development by strengthening claims regarding the relationship between SRSD instruction, autonomy, and writing proficiency.